Contribution of the Major ND10 Proteins PML, hDaxx and Sp100 to the Regulation of Human Cytomegalovirus Latency and Lytic Replication in the Monocytic Cell Line THP-1 - Wagenknecht, Nadine; Reuter, Nina; Scherer, Myriam; Reichel, Anna; Müller, Regina; Stamminger, Thomas (Viruses, 2015)
Promyelocytic leukemia nuclear bodies, also termed nuclear domain 10 (ND10), have emerged as nuclear protein accumulations mediating an intrinsic cellular defense against viral infections via chromatin-based mechanisms, however, their contribution to the control of herpesviral latency is still controversial. In this study, we utilized the monocytic cell line THP-1 as an in vitro latency model for human cytomegalovirus infection (HCMV). Characterization of THP-1 cells by immunofluorescence andWestern blot analysis confirmed the expression of all major ND10 components. THP-1 cells with a stable, individual knockdown of PML, hDaxx or Sp100 were generated. Importantly, depletion of the major ND10 proteins did not prevent the terminal cellular differentiation of THP-1 monocytes. After construction of a recombinant, endotheliotropic human cytomegalovirus expressing IE2-EYFP, we investigated whether the depletion of ND10 proteins affects the onset of viral IE gene expression. While after infection of differentiated, THP-1-derived macrophages as well as during differentiation-induced reactivation from latency an increase in the number of IE-expressing cells was readily detectable in the absence of the major ND10 proteins, no effect was observed in non-differentiated monocytes. We conclude that PML, hDaxx and Sp100 primarily act as cellular restriction factors during lytic HCMV replication and during the dynamic process of reactivation but do not serve as key determinants for the establishment of HCMV latency.
EVALuna2:8283

Small ubiquitin-related modifier (SUMO) pathway-mediated enhancement of human cytomegalovirus replication correlates with a recruitment of SUMO-1/3 proteins to viral replication compartments - Scherer, Myriam; Reuter, Nina; Wagenknecht, Nadine; Otto, Victoria; Sticht, Heinrich; Stamminger, Thomas (Journal of General Virology, 2013)
Recent studies have suggested that the small ubiquitin-related modifier (SUMO) conjugation pathway may play an important role in intrinsic antiviral resistance and thus for repression of herpesviral infections. In particular, it was shown that the herpes simplex virus type-1 regulatory protein ICP0 acts as a SUMO-targeted ubiquitin ligase (STUbL), inducing the widespread degradation of SUMO-conjugated proteins during infection. As the IE1 protein of human cytomegalovirus (HCMV) is known to mediate a de-SUMOylation of PML, we investigated whether HCMV uses a similar mechanism to counteract intrinsic antiviral resistance. We generated primary human fibroblasts stably expressing FLAG-SUMO-1 or FLAG-SUMO-3 and analysed the SUMOylation pattern after HCMV infection or isolated IE1 expression. However, Western blot experiments did not reveal a global loss of SUMO conjugates, either in HCMV-infected or in IE1-expressing cells, arguing against a function of IE1 as an STUbL. Interestingly, we observed that FLAG-SUMO-1 and FLAG-SUMO-3, subsequent to IE1-mediated promyelocytic leukemia protein (PML) de-SUMOylation and the consequent disruption of PML nuclear bodies, were recruited into viral replication compartments. This raised the question of whether FLAG-SUMO-1/3 might promote HCMV replication. Intriguingly, overexpression of FLAG-SUMO-1/3 enhanced accumulation of viral DNA, which correlated with an increase in viral replication and in virus particle release. Together, these data indicate that HCMV, in contrast to other herpesviruses, has evolved subtle mechanisms enabling it to utilize the SUMO conjugation pathway for its own benefit, resulting in an overall positive effect of SUMO conjugation for HCMV replication.
EVALuna2:8191